Accuracy of High Resolution Digital Cartographic Products with Elevation Control Points - de Souza, Mauricio; Siqueira, Henrique Lopes; Araujo, Márcio Santos; de Oliveira, Lucas Yuri Dutra; Gonçalves, Wesley Nunes; Ramos, Ana Paula Marques [UNESP]; Junior, José Marcato (Universidade Federal do Rio de Janeiro, 2025)
The use of Unmanned aerial vehicles (UAVs) as a tool for image acquisition has been applied in several fields, some applications require cartographic products with high accuracy. With this comes the need for planning the acquisition of images and distribution of control points (GCP) so that digital products meet the required level of accuracy. The aim of this work was to investigate whether the quantity of control points as well as their distribution in different altitude planes in elevated ground can improve the accuracy of the generated cartographic products. RGB images captured by an onboard camera with a resolution of 20 MP were used. Images were captured by a multirotor UAV with an overlap of 80% (front and side) and estimated GSD of 0.017 m. The surveyed area of 5.5 ha overflown area had 31 targets surveyed with GNSS RTK, 21 defined as checkpoints (CP) and 12 as ground control points (GCP), which were used in image processing to generate orthomosaic. We evaluated the accuracy of the generated products based on the PEC-PCD. The results showed that when using only 2 GCPs the altimetric errors are high, being the single configuration that did not fit the PEC-PCD scale 1: 1,000 class A. With 5 GCPs we obtained the best RMSE in altimetry (0.026 m). With 6 GCPs we obtained the best RMSE in planimetry (0.046 m). Altimetry is the most sensitive aspect in generating cartographic products, and the use of GCPs in elevation improves altimetric accuracy.
Acurácia de Produtos Cartográficos Digitais de Alta Resolução com Pontos de Controle em Elevação
Keywords: GCP; PEC-PCD; UAV